MENGENAL KHAZANAH MUSHAF KUDUS - Dodi Adrian Febriansyah (JURNAL ILMIAH NUSANTARA, 2026)
The Qur'an is the Word of Allah revealed to the Prophet Muhammad PBUH by bringing great miracles and various characteristics of diversity in the Qur'an. The Qur'an is certainly inseparable from physical study and extensive knowledge. Seeing the advanced development of the Qur'an physically and authorship, it continues to develop along with the systematics of the authorship of the Qur'an. One of them is Mushaf Kudus which is famous as Mushaf Huffadz). The first time this mushaf came when K.H. Arwani Amin got a mushaf at the time of Hajj. Therefore, the purpose of this study is to review the history of the Holy Mushaf and the physical characteristics of the Mushaf to the science that makes it easier for many huffadz to use it. This study uses a qualitative methodology with the type of literature review research (libarary search) by collecting relevant data that is in accordance with the topic of discussion. The results of this study show that the Mushaf Kudus is a copy of the Mushaf that is reprinted for dissemination. This holy mushaf became an icon as the mushaf of the memorizers of the Qur'an was originally a fairly old Bahriyah Mushaf. The characteristics of this holy mushaf contain a complete 30 juz and 114 surahs with a page thickness of 619 numbered pages. surah Al-Fatihah as the beginning of the surah listed on page 2 and surah An-Nas as the closing of the surah. As for harakat and punctuation, of course, the use is also familiar and applies to all circles of Indonesian society, fathah, kasrah, dhammah, fathatain, kasratain, dhommatain. Meanwhile, the use of the type of khat in the writing of this holy mushaf is khat naskhi, and the use of rasm in this holy mushaf uses a mixed rasm between Imla'i and Usmani.